In vivo antitussive activity of Coccinia grandis against irritant aerosol and sulfur dioxide-induced cough model in rodents - Shakti Prasad Pattanayak; Priyashree Sunita (Bangladesh Pharmacological Society, 2009)
Cocciniagrandis (Cucurbitaceae) has extensively used to get relief from asthma and cough by the indigenous people of India. The antitussive effect of aerosols of two different concentrations (2.5%, 5%w/v) of methanol extract of C. grandis fruits were tested by counting the numbers of coughs produced due to aerosols of citric acid, 10 min after exposing the male guinea pigs to aerosols of test solutions for 7 min. In another set of experiment methanol extract was investigated for its therapeutic efficacy on a cough model induced by sulfur dioxide gas in mice. The results showed significant reduction of cough number obtained in the presence of both concentrations of methanol extract as that of the prototype antitussive agent codeine phosphate. Also, methanol extract exhibited significant antitussive effect at 100, 200 and 400 mg/kg, per orally by inhibiting the cough by 20.57, 33.73 and 56.71% within 90 min of performing the experiment.